(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article is devoted to the essence of the communicative-activity approach and the algorithm for the transition to a competency-based approach in teaching Russian as a foreign language. The implementation of a communicative approach to teaching Russian in pairs based on modern technologies naturally correlates with the problem of forming a student of a non-linguistic university as a linguistic personality who owns all types of speech activity, ensuring the formation of skills and abilities in listening, reading, speaking, which are able to solve various problems in generalization process.